(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Rice is considered a wholesome cereal grain that is ideal for the many nutritional needs owing to its significance in human nutrition by providing bulk of calories and few micronutrients requirement for more than half of the world’s population. The aim of this study was to evaluate the nutritional composition and anti-nutritional contents of different local rice varieties cultivated in Dandume Local Government Area, Katsina State. Nutritional and anti-nutritional contents of the rice samples were determined. The percentage moisture contents of Yar yarima and Farar cikin ja were significantly high (p<0.05) than the other rice varieties recorded 12.05-13.55%. But the percentage fat contents of the rice varieties were not significantly different (p>0.05) ranged from 0.89-1.25%. The percentage crude protein contents of the rice varieties were not significantly different (p>0.05) recorded 8.31-9.31%. However, the carbohydrate content was not significantly different (p>0.05) among the rice varieties ranges from 75.36% - 81.18%. There were significant differences (p<0.05) in calcium, magnesium, potassium, sodium and iron contents among the rice varieties recorded 158.29 - 219.69 (mg/100g), 33.34 - 44.26 (mg/100g), 75.47 - 92.25 (mg/100g), 23.71 - 29.22 mg/100g and 62.70 96.89 (mg/100g) respectively. The total phytate contents of the rice samples recorded 0.91 1.59% which were below the reference range (3.6), while the total oxalate contents ranged from 22.75 - 44.62% and these were above the reference range (<1.25). This study confirmed varietal influence of the nutritional and anti-nutritional compositions of different local rice varieties which may contribute to the daily requirement.